Using Dental Health Care Personnel During a Crisis: COVID-19 Pandemic in the Bronx, New York. (March 2021) - Badner, Victor; Saraghi, Mana
The first few months of the coronavirus disease 2019 (COVID-19) pandemic challenged health care facilities worldwide in many ways. Inpatient and intensive care unit (ICU) beds were at a premium, and personnel shortages occurred during the initial peak of the pandemic. New York State was the hardest hit of all US states, with a high concentration of cases in New York City and, in particular, Bronx County. The governor of New York and leadership of hospitals in New York City called upon all available personnel to provide support and patient care during this health care crisis. This case study highlights the efforts of Jacobi Medical Center, located in the northeast Bronx, from March 1 through May 31, 2020, and its use of nontraditional health care personnel, including Department of Dentistry/OMFS (Oral and Maxillofacial Surgery) staff members, to provide a wide range of health care services. Dental staff members including ancillary personnel, residents, and attendings were redeployed and functioned throughout the facility. Dental anesthesiology residents provided medical services in support of their colleagues in a step-down COVID-19–dedicated ICU, providing intubation, ventilator management, and critical and palliative care. (Step-down units provide an intermediate level of care between ICUs and the general medical–surgical wards.) Clear communication of an acute need, a well-articulated mission, creative use of personnel, and dedicated staff members were evident during this challenging time. Although not routinely called upon to provide support in the medical and surgical inpatient areas, dental staff members may provide additional health care personnel during times of need.